Between civilization & barbarism : women, nation, and literary culture in modern Argentina - Masiello, Francine (Engendering Latin America, 1992)
"Between Civilization and Barbarism explores the positioning of women within the Argentine nation and argues that women neither sought alliance with the "civilizing" agenda of leading statesmen nor found identity in the extreme poses of barbarism to which some intellectuals had condemned them. Instead, women used literary and political texts to surpass the neatly outlined roles assigned them."--BOOK JACKET. "Beginning with literary and journalistic texts written by and about women from the time of Sarmiento, Francine Masiello traces strategic shifts in the discourse on gender at moments of national crisis. She considers not only novels and guides to female behavior written by and for privileged women but also newspapers and political tracts produced by women of the working classes."--BOOK JACKET. "Extending her study into the urban expansion and modernization of the 1920s, Masiello explores the nature of gender relations posited in treatises' or crime and public disorder and in the texts of avant-garde and social-realist writers. In addressing such representations of women, as well as the effects of ideology and history on writing, Masiello offers bold new insights into the development of Latin American women's literature and illuminating the role of women informing the culture of present-day Argentina."--Jacket